1990
DOI: 10.1099/00221287-136-7-1429
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the gene for the "19 kDa" antigen of Mycobacterium bovis

Abstract: Monoclonal antibody CMA134.1 reacted with a protein antigen of apparent molecular mass 22 kDa from Mycobacterium bovis and Mycobacterium tuberculosis, and with an apparently 24 kDa antigen of Mycobacterium kansasii, but not with other mycobacteria or related species. This antibody was used to screen a gene library of M. bovis in Agtll and identified a recombinant clone that expressed a protein with an apparent molecular mass of 1% 20 kDa. Gene expression occurred from the lac promoter in lgtll, but used an uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…In this regard, a relatively lower virulence of naturally mutated M. tuberculosis strains that do not express the 19kDa protein has been described in an in vivo murine model of M. tuberculosis infection [37]. Because it has been reported that, within the M. tuberculosis complex, the 19-kDa gene was found to be conserved [38,39], the present study aimed to determine the relevance of the mycobacterial 19-kDa lipoprotein in induction of apoptosis. We demonstrated that, after infection with 19KO M. tuberculosis and BCG, MDM cell death was reduced (by nearly 70%), compared with apoptosis induced by wt strains.…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, a relatively lower virulence of naturally mutated M. tuberculosis strains that do not express the 19kDa protein has been described in an in vivo murine model of M. tuberculosis infection [37]. Because it has been reported that, within the M. tuberculosis complex, the 19-kDa gene was found to be conserved [38,39], the present study aimed to determine the relevance of the mycobacterial 19-kDa lipoprotein in induction of apoptosis. We demonstrated that, after infection with 19KO M. tuberculosis and BCG, MDM cell death was reduced (by nearly 70%), compared with apoptosis induced by wt strains.…”
Section: Discussionmentioning
confidence: 95%
“…In an effort to study mutations conferring protein export defects in mycobacteria, we constructed a Tn5370 library in a reporter strain of M. smegmatis, mc 2 1279 (Table 1). The reporter strain, mc 2 1279, was designed to constitutively express and export a recombinant fusion of the secreted M. tuberculosis 19-kDa antigen (LpqH) (15,23) and the truncated E. coli PhoA (ЈPhoA). The secreted fusion protein was detected by its extracellular alkaline phosphatase activity, assayed by blue color production on plates containing the chromogenic substrate of PhoA, BCIP.…”
Section: Resultsmentioning
confidence: 99%
“…The negative control strain used in these assays was M. smegmatis mc 2 155 phoA::hyg. The effect of inorganic phosphate on phoA induction was studied at low (500 M) and high (10 mM) concentrations of phosphate in the medium as suggested before (15,30), with some modifications. The strains were grown in 7H9 medium (Difco) to an optical density at 600 nm of 1.0, and then the cultures were washed twice with 500 M phosphate buffer and the cells were resuspended to a final optical density at 600 nm of 0.2 in a home-prepared 7H9 medium containing either 500 M or 10 mM K 2 NaH 2 PO 4 buffer, pH 7.0.…”
Section: Methodsmentioning
confidence: 99%
“…There is a n increasing interest in these antigens t o prepare new generation anti-TB vaccines ( O r m e 1988; Pal & Horwitz, 1992;Andersen, 1994) However, certain non-secreted proteins, such as membrane-associated, cell-wall-associated or cytoplasmic (Andersen & Brennan, 1994) (Lee e t al., 1991) are the most studied M. tuberculosis membrane antigens (Ashbridge, 1989;Collins et al, 1990;Faith et al, 1991;Booth e t al., 1993;Prestidge e t al., 1995).…”
Section: Ajooosoomentioning
confidence: 99%